Phocine distemper virus (PDV) seroprevalence as predictor for future outbreaks in harbour seals - Ludes-Wehrmeister, E.; Dupke, C.; Harder, Timm C.; Baumgärtner, W.; Haas, L.; Teilmann, J.; Dietz, R.; Jensen, L.F.; Siebert, U. (Veterinary Microbiology, 2015)
Phocine distemper virus (PDV) infections caused the two most pronounced mass mortalities in marine mammals documented in the past century. During the two outbreaks, 23,000 and 30,000 harbour seals (Phoca vitulina), died in 1988/89 and 2002 across populations in the Wadden Sea and adjacent waters, respectively. To follow the mechanism and development of disease spreading, the dynamics of morbillivirus-specific antibodies in harbour seal populations in German and Danish waters were examined. 522 serum samples of free-ranging harbour seals of different ages were sampled between 1990 and 2014. By standard neutralisation assays, morbillivirus-specific antibodies were detected, using either the PDV isolate 2558/Han 88 or the related canine distemper virus (CDV) strain Onderstepoort. A total of 159 (30,5%) of the harbour seals were seropositive. Annual seroprevalence rates showed an undulating course: Peaks were seen in the post-epidemic years 1990/1991 and 2002/2003. Following each PDV outbreak, seroprevalence decreased and six to eight years after the epidemics samples were tested seronegative, indicating that the populations are now again susceptible to new PDV outbreak. After the last outbreak in 2002, the populations grew steadily to an estimated maximum (since 1975) of about 39,100 individuals in the Wadden Sea in 2014 and about 23,540 harbour seals in the Kattegat area in 2013. A re-appearence of PDV would presumably result in another epizootic with high mortality rates as encountered in the previous outbreaks. The current high population density renders harbour seals vulnerable to rapid spread of infectious agents including PDV and the recently detected influenza A virus.